A case with oto-spondylo-mega-epiphyseal-dysplasia (OSMED): the clinical recognition and differential diagnosis - Karaer, Kadri; Rosti, Rasim Özgür; Torun, Deniz; Sanal, Hatice Tuba; Bahçe, Muhterem; Güran, Şefik (The Turkish Journal of Pediatrics, 2011)
The oto-spondylo-mega-epiphyseal-dysplasia (OSMED) phenotype is an autosomal recessive trait that is a skeletal dysplasia with the hallmark findings of limb shortening, multiple skeletal and radiological abnormalities, mid-face hypoplasia with a flat nasal bridge, small upturned nasal tip, and sensorineural hearing loss. A 3.5-year-old girl born to consanguineous Turkish parents had characteristic facial features at birth: mid-face hypoplasia, mild hypertelorism, upslanting palpebral fissures, prominent supraorbital ridges, depressed nasal bridge, small upturned nasal tip, long philtrum, and micrognathia. Radiological examination at three years of age revealed large flaring metaphyses and wide flat epiphyses. The humerus and femur showed the characteristic dumbbell shape. She had bilateral hearing loss with no ophthalmologic findings. There is continuing debate over the clinical overlap and differential diagnosis of OSMED syndrome. The patient was examined considering Weissenbacher-Zweymuller, Stickler type 3, Marshall syndrome, and Kniest dysplasia as possible differential diagnoses. We believe that the presented patient clinically manifested features of OSMED syndrome. We would like to point out that the management of OSMED calls for a coordinated multidisciplinary approach.